Alterations of the immune transcriptome in resistant and susceptible hard clams (Mercenaria mercenaria) in response to Quahog Parasite Unknown (QPX) and temperature. (February 2016) - Wang, Kailai; Pales Espinosa, Emmanuelle; Tanguy, Arnaud; Allam, Bassem
Abstract: Quahog Parasite Unknown (QPX) is a fatal protistan parasite that causes severe losses in the hard clam ( Mercenaria mercenaria ) fisheries along the northeastern coast of the US. Field and laboratory studies of QPX disease have demonstrated a major role for water temperature and M. mercenaria genetic origin in disease development. Infections are more likely to occur at cold temperatures, with clam stocks originating from southern states being more susceptible than clams from northern origin where disease is enzootic. Even though the influence of temperature on QPX infection have been examined in susceptible and resistant M. mercenaria at physiological and cellular scales, the underlying molecular mechanisms associated with host–pathogen interactions remain largely unknown. This study was carried out to explore the molecular changes in M. mercenaria in response to temperature and QPX infection on the transcriptomic level, and also to compare molecular responses between susceptible and resistant clam stocks. A M. mercenaria oligoarray (15 K Agilent) platform was produced based on our previously generated transcriptomic data and was used to compare gene expression profiles in naive and QPX-infected susceptible (Florida stock) and resistant (Massachusetts) clams maintained at temperatures favoring disease development (13 °C) or clam healing (21 °C). In addition, transcriptomic changes reflecting focal (the site of infection, mantle) and systemic (circulating hemocytes) responses were also assessed using the oligoarray platform. Results revealed significant regulation of multiple biological pathways by temperature and QPX infection, mainly associated with immune recognition, microbial killing, protein synthesis, oxidative protection and metabolism. Alterations were widely systemic with most changes in gene expression revealed in hemocytes, highlighting the role of circulating hemocytes as the first line of defense against pathogenic stress. A large number of complement-related recognition molecules with fibrinogen or C1q domains were shown to be specially induced following QPX challenge, and the expression of these molecules was significantly higher in resistant clams as compared to susceptible ones. These highly variable immune proteins may be potent candidate molecular markers for future study of M. mercenaria resistance against QPX. Beyond the specific case of clam response to QPX, this study also provides insights into the primitive complement-like system in the hard clam. Graphical abstract: Differentially expressed (DE) transcripts in resistant and susceptible clams in response to QPX under different temperature conditions Highlights: QPX infection regulated the transcription of clam immune genes. Temperature strongly modulated clam response to QPX. Transcripts induced by QPX were enriched with highly variable immune recognition receptors. Resistant clams expressed higher levels of immune receptors as compared to susceptible ones.